Mitos Perempuan dalam Meme Al-Qur'an: Kajian Semiotika Media Sosial - Nadia, Matsna Afwi (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2022)
This article explores the phenomenon of mythologizing Qur'anic memes on social media platforms, employing Roland Barthes' semiotic analysis as a theoretical framework. The focus of this study is the examination of the Qur'anic meme pertaining to the theme of women's deceit. The extent to which the interpretation of the Qur'an depicted in the meme gives rise to myths that obfuscate its original meaning will be examined. This study has a specific objective of addressing three inquiries: firstly, the manner in which verses are interpreted within the context of the meme depicting women's deceit; secondly, the myths encompassed within the meme illustrating women's deceit; and thirdly, the implications that arise from the mythologization of memes in relation to the interpretation of the Qur'an. To address these three concerns, this study employs a descriptive-analytical approach utilising Roland Barthes' semiotic framework. Consequently, the meme illustrates a myth that arises from the amalgamation of the interpretations of Al-Nisā'[4]: 76 and Yūsuf [12]: 28, suggesting that the allure of women holds greater sway than the allure of Satan. The perpetuation of the myth engenders a sense of cynicism towards women, thereby reinforcing the prevalence of misogynistic interpretations.